A novel fuzzy neural ensemble decision support system for whisper cancer analysis - Chin, Pei Loon. (2010)
Early detection of ovarian cancer is critical to allow women to seek treatment when the cancer is still in the early stages, which will increase their chances of survival. Unfortunately, detection tools available now are either too expensive or they do not have enough sensitivity and specificity.